PEMAHAMAN HADIS LARANGAN BERBICARA KETIKA DI KAMAR MANDI (STUDI VALIDITAS DALAM KITAB AT-TARGHIB WA AT-TARHIB KARYA AL-MUNDZIRI) - Etika Noviyanti; Uswatun Hasanah; Sulaiman M. Nur (CV DOKI COURSE AND TRAINING, 2023)
This article aims to examine the validity of the hadith regarding the prohibition of talking while in the bathroom in al-Mundziri's At-Targhib Wa At-Tarhib